Online learning experiences of female students living with albinism amidst a global pandemic: evidence from South Africa and Zimbabwe - Makura, Alfred H.; Zireva, Davison (Frontiers in Education, 2024)
Our paper explores the online learning experiences of two female students living with Albinism in South Africa and Zimbabwe during the COVID-19 era. Using a two-case qualitative research design, we conducted in-depth face to face interviews with the purposefully selected sample. The intention was to bring to the fore, the unique online experiences of female students living with Albinism. Data were thematically analysed. Literature suggests that the unique health and physiological characteristics of students living with Albinism tend to present unique but surmountable challenges. Our study established that the gender and physiology of the students tended to complicate or enhance their desire to benefit from online learning during the COVID-19 era. The findings make a case for academic inclusion in universities' academic projects. Institutions may consider instituting pedagogically inclusive online learning mechanisms that are not only gender sensitive, but are in sync with, not only the COVID-19 realities, but similar calamities. accepted that the COVID-19 pandemic disrupted education worldwide, with many schools and universities transitioning to remote learning (Smith, 2020). Female students with albinism, face unique challenges in accessing online education. Hence, this paper seeks to explore the online learning experiences of female students with albinism during the COVID-19 era.